Analysis of Airport Officers' Preparedness at Yogyakarta International Airport in Facing Potential Tsunami Hazards - Delia Puspa Nirwana; Annike Resty Putrie (CV. Rayyan Dwi Bharata, 2023)
Indonesia is a country that has a geological location where three plates meet and two oceans meet. Because of its geological location, Indonesia is a country that is vulnerable to disasters such as the tsunami disaster. Therefore, preparedness is needed to deal with these potential hazards. Preparedness is a series of activities carried out to anticipate disasters through appropriate and efficient steps. Preparedness is emphasized on the ability to take preparatory actions to face disaster emergencies quickly and precisely. At airports that are located in disaster-prone areas, of course, the preparedness of airport officers is of utmost concern. This preparedness can be in the form of training such as simulations and outreach. In addition to preparedness, preparation for disaster mitigation is also needed. This disaster mitigation can be in the form of constructing disaster-resistant buildings, installing evacuation signs and also making policies that are carried out when a disaster occurs. This study uses qualitative methods with data collection techniques through interviews, observation, and documentation. Then proceed with data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results shown in this study are that the preparedness of airport officers at Yogyakarta International Airport has been very well prepared, namely by conducting training with related parties and also local residents. In addition, work instructions were also prepared so that they could be used as guidelines in the event of a tsunami disaster. Yogyakarta International Airport has prepared structural and non-structural disaster mitigation. This structural mitigation is in the form of building a building that can withstand an earthquake of 8.8 magnitude and a tsunami of 12 meters, making green belts, installing evacuation route signs, and activating an early warning system. The non-structural mitigation set at this airport is making policies that regulate how to mobilize resources during and after a disaster occurs and data on the amount of available resources. After the disaster, how the airport will be operated will be seen how big the impact is on the airport area.